Aboriginal Title After Tsilhqot’in: What We Know, What We Think We Know, and What We Still Need to Know More About - Porter, Jared; Quig, Paula (Les Cahiers de droit, 2023)
With the ten-year anniversary of Tsilhqot’in on the horizon, the time is ripe to consider the impact of this monumental decision as well as some key questions that remain in its wake. This article surveys the legal situation following Tsilhqot’in and identifies some major issues likely to require attention in the future. This is done by examining what we know about Aboriginal title following Tsilhqot’in, in the sense of what seems clear following the decision, what we think we know about Aboriginal title, in the sense of what we put forward as reasonable interpretations flowing from the decision and, finally, what we need to know more about following Tsilhqot’in. In this last section, the article examines Aboriginal title and private land interests as well as Aboriginal title to submerged lands.